2018
DOI: 10.1002/cmdc.201800566
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the Benzylpiperidine Moiety with Fluorinated Phenylalkyl Side Chains for the Development of GluN2B Receptor Ligands

Abstract: The 4‐benzylpiperidine moiety is a central structural element of potent N‐methyl‐d‐aspartate (NMDA) receptor antagonists containing the GluN2B subunit. To obtain novel GluN2B ligands suitable for positron emission tomography, the benzylpiperidine moiety was replaced with fluorinated ω‐phenylalkylamino groups. For this purpose three primary propyl‐ and butylamines 7 a–c and one butyraldehyde 7 d bearing a fluorine atom and an ω‐phenyl moiety were prepared in 3‐ to 7‐step syntheses. Compounds 7 a–d were attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…101,606 (Chenard et al, 1995), radiprodil (Mullier et al, 2017), Merck-20j, andMK-0657 (Liverton et al, 2007;Addy et al, 2009) (Table 10). Alternative scaffolds include propanolamines (Tahirovic et al, 2008), benzimidazoles (McCauley et al, 2004;Davies et al, 2012), cyclic benzamidines (Nguyen et al, 2007), amino cyclopentanes (Layton et al, 2011), piperidinyl pyrrolidinones (Marcin et al, 2018), and other compounds (Claiborne et al, 2003;McIntyre et al, 2009;Mosley et al, 2009;Brown et al, 2011;Beinat et al, 2014;Buemi et al, 2014;Bristow et al, 2017;Dey et al, 2018;Thum et al, 2018;Zscherp et al, 2018;Zampieri et al, 2019;Zhang et al, 2019). Molecules with two aromatic rings separated by a linker also cross over to act selectively on GluN2B, including the dopamine receptor antagonist haloperidol, the r and dopamine receptor antagonist trifluperidol, the H 3 histamine receptor antagonists clobenpropit and iodophenpropit, the b-adrenergic receptor agonist nylidrin, and the TRPV1 receptor antagonist capsazepine (Supplemental Table 13).…”
Section: B Nmda Receptor Modulatorsmentioning
confidence: 99%
“…101,606 (Chenard et al, 1995), radiprodil (Mullier et al, 2017), Merck-20j, andMK-0657 (Liverton et al, 2007;Addy et al, 2009) (Table 10). Alternative scaffolds include propanolamines (Tahirovic et al, 2008), benzimidazoles (McCauley et al, 2004;Davies et al, 2012), cyclic benzamidines (Nguyen et al, 2007), amino cyclopentanes (Layton et al, 2011), piperidinyl pyrrolidinones (Marcin et al, 2018), and other compounds (Claiborne et al, 2003;McIntyre et al, 2009;Mosley et al, 2009;Brown et al, 2011;Beinat et al, 2014;Buemi et al, 2014;Bristow et al, 2017;Dey et al, 2018;Thum et al, 2018;Zscherp et al, 2018;Zampieri et al, 2019;Zhang et al, 2019). Molecules with two aromatic rings separated by a linker also cross over to act selectively on GluN2B, including the dopamine receptor antagonist haloperidol, the r and dopamine receptor antagonist trifluperidol, the H 3 histamine receptor antagonists clobenpropit and iodophenpropit, the b-adrenergic receptor agonist nylidrin, and the TRPV1 receptor antagonist capsazepine (Supplemental Table 13).…”
Section: B Nmda Receptor Modulatorsmentioning
confidence: 99%
“…Since the discovery of GluN2B-selective antagonists, numerous scaffolds of highly selective GluN2B NMDA receptor antagonists have been reported (reviewed by Layton et al, 2006;Mony et al, 2009;Koller and Urwyler, 2010;Ruppa et al, 2012). These include phenethanolamines such as ifenprodil (Williams, 1993), eliprodil (Carter et al, 1988), radiprodil (Michel et al, 2014;Auvin et al, 2020), traxoprodil (Chenard et al, 1995), Ro 25-6981 (Fischer et al, 1997), MK-0657 (Addy et al, 2009), plus additional scaffolds including propanolamines (Yuan et al, 2015), benzimidazoles (McCauley et al, 2004;Davies et al, 2012), cyclic benzamidines (Nguyen et al, 2007), amino cyclopentanes (Layton et al, 2011), piperidinyl pyrrolidinones (Marcin et al, 2018), and other compounds (Mosley et al, 2009;McIntyre et al, 2009;Brown et al, 2011;Buemi et al, 2014;Dey et al, 2018;Thum et al, 2018). Whereas crystallographic evaluation of ifenprodil at the GluN1/GluN2B heterodimer amino terminal domain (ATD) interface (Karakas et al, 2014) is the likely pose for many GluN2B-selective inhibitors, recent structural data revealed a unique region within the binding cavity that can be occupied by compounds with a more compact scaffold (Kemp and Tasker, 2009;Stroebel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ketones 5a‐f with different substituents in 2‐position were reductively aminated at 7‐position with various primary amines 6a‐e to obtain the desired secondary amines 9c,e , 10a‐c,e , 11d , 12a‐c , 13c , and 14a (Scheme ). The syntheses of fluorinated phenylpropylamine 6a as well as in β‐ and γ‐position fluorinated phenylbutylamines 6b and 6c have already been reported . To evaluate the effect of the F‐atom in the phenylalkyl side chain on the GluN2B affinity and selectivity over related receptors, nonfluorinated analogues were also synthesized by reductive amination of ketones 5a‐f with phenylpropyl‐ and phenylbutylamine 6d and 6e , respectively.…”
Section: Synthesismentioning
confidence: 99%
“…In a previous study, we have shown that an F‐atom in the side chain of benzo[7]annulen‐7‐amines is well tolerated by GluN2B subunit containing NMDARs . Furthermore, a scaffold hopping approach led to the result that benzo[7]annulene derivatives are in combination with fluorinated phenylalkyl side chains superior to other scaffolds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation